Transcriptomic study of the role of MeFtsZ2-1 in pigment accumulation in cassava leaves - Zang, Yuwei; Wu, Kunlin; Liu, Liangwang; Ran, Fangfang; Wang, Changyi; Wu, Shuwen; Wang, Dayong; Guo, Jianchun; Min, Yi (BMC genomics, 2024)
MeFtsZ2-1 is a key gene for plant plastid division, but the mechanism by which MeFtsZ2-1 affects pigment accumulation in cassava ( Manihot esculenta Crantz) through plastids remains unclear. We found that MeFtsZ2-1 overexpression in cassava (OE) exhibited darker colors of leaves, with increased levels of anthocyanins and carotenoids. Further observation via Transmission Electron Microscopy (TEM) revealed no apparent defects in chloroplast structure but an increase in the number of plastoglobule in OE leaves. RNA-seq results showed 1582 differentially expressed genes (DEGs) in leaves of OE. KEGG pathway analysis indicated that these DEGs were enriched in pathways related to flavonoid, anthocyanin, and carotenoid biosynthesis. This study reveals the role of MeFtsZ2-1 in cassava pigment accumulation from a physiological and transcriptomic perspective, providing a theoretical basis for improving cassava quality.